Development of a semi-analytical model to select a suitable airfoil section for blades of horizontal axis hydrokinetic turbine. (February 2020) - Gupta, Mahendra Kumar; Subbarao, P.M.V.
Abstract: All modern hydro-kinetic turbines are being designed based on a lift, using airfoils, which should have a significant lift to drag ratio to achieve maximum efficiency.SG604X family airfoil has significant lift-to-drag ratio under an operating range of Re from 1 0 5 – 1 0 6, which also come under our working conditions. Blade Element Momentum (BEM) theory was used to obtain optimum blade shape. The iterative numerical approach was used in MATLAB to calculate optimized blade profile and coefficient of performance ( C p ). After grid independency test, finally k- ω shear stress transport (SST) and the k-є model with enhanced wall treatment were used for calculation of the lift coefficient and the drag coefficient of airfoil SG6043. The performance of the rotor overall expected tip speed ratio (T.S.R ( λ )) was calculated and found that maximum C p, m a x is 0.51 at optimum λ o p t of 5. The suitability of SG6043 airfoil over NACA0012 airfoil in our case has been shown.